Breastmilk Production of Mother with Post Caesarean Section Given Oketani and Oxitocyn Massage - Machmudah Machmudah; Nikmatul Khayati (Jurnal Ners, 2014)
Introduction: Oketani massage and oxytocin is one of the breast care methods that do not cause pain. Massage can stimulate oketani pectoralis muscle strength to increase milk production and make the breasts become more soft and elastic so meumudahkan baby to suck milk. Massage oketani will also provide a sense of relief and an overall comfortable on respondents, improving the quality of breast milk, to prevent mastitis and nipple blisters and can fi x / reduce lactation problems caused by putting a fl at (fl at nipples), nipples that enter into (inverted).Methods: This research was a quasi experimental with post test only design.Results: The results showed that there are different breastfeeding frequency, frequency of bowel, bladder frequency of respondents who do massage and oxytocin oketani. Conclusion: one milk production assessment is to assess the frequency and volume of urine bladder baby. Normal babies will urinate 6-8 times a day, with a clear yellow color of urine is urine volume between 30-50 mg daily. This result is consistent with research conducted by Budiarti (2009) and Mardianingsih (2010) which states that the milk production can be judged from the frequency of micturition babies as many as 6-8 times a day